2013
DOI: 10.1002/jbm.a.35000
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cardiac extracellular matrix scaffolds by decellularization of human myocardium

Abstract: Extracellular matrix (ECM) derived by tissue decellularization has applications as a tissue engineering scaffold and for support of cellular regeneration. Myocardial ECM from animals has been produced by whole-organ perfusion or immersion processes, but methods for preparation of human myocardial ECM for therapy and research have not been compared in detail, yet. We analyzed the impact of decellularization processes on human myocardial ECM, and tested its ability to serve as a scaffold for cell seeding. Sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 47 publications
1
87
0
4
Order By: Relevance
“…In the present study, perfusion decellularization of human hearts resulted in acellular scaffolds consisting of major extracellular matrix components such as collagens, elastin, and glycosaminoglycans, which is in line with similar data published in other organ systems and species 15, 36, 37 , and decellularized human heart sections 52 . Quantitative analyses of extracellular matrix components were similar in DCD and DBD hearts, with preservation of insoluble collagen and glycosaminoglycans, and reduction of soluble collagen and elastin.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, perfusion decellularization of human hearts resulted in acellular scaffolds consisting of major extracellular matrix components such as collagens, elastin, and glycosaminoglycans, which is in line with similar data published in other organ systems and species 15, 36, 37 , and decellularized human heart sections 52 . Quantitative analyses of extracellular matrix components were similar in DCD and DBD hearts, with preservation of insoluble collagen and glycosaminoglycans, and reduction of soluble collagen and elastin.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, while the valves from the MSC group were found to have similar ECM organization to native pulmonary valves, mononuclear cell-seeded valves underwent significant valve thickening and inflammatory cell infiltration (374). Human myocardial ECM sheets derived from tissue decellularization have been analyzed and deemed to be suitable biologic scaffolds for cell seeding and cell-matrix interaction studies (257). Using a translational approach, Huang et al (154) found that fabricated autologous bone marrow-derived MSC sheet fragments, which retained endogenous ECM, preserved cardiac function and attenuated fibrosis LV and remodeling compared with control when transplanted into infarcted porcine hearts.…”
Section: Decellularization and Recellularizationmentioning
confidence: 99%
“…In an attempt to quantitatively standardize decellularization results, Crapo et al reviewed general parameters with an emphasis on minimizing residual DNA. Though decellularization techniques have thus far been unable to remove 100% of cell material in larger animal model and human hearts [14][15][16], these parameters all focus on limiting nucleic material since residual DNA is directly correlated to adverse host reactions and may contribute to cytocompatibility issues upon reintroduction of cells [31,32]. Prior to the use of nucleases to remove DNA, we were interested in the effectiveness of retrograde perfusion through the aorta and wanted to identify which regions had higher residual DNA content.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to tissue engineering is the decellularization-recellularization method [5,6]. This method has been successful in regenerating skin, bladders, bone, kidneys [7], liver [8], vessels and lungs [9][10][11]; however, the same level of success has been much more difficult to achieve in organs with functional units, such as the heart [12][13][14][15][16][17]. The vascularization, high metabolic demand and the low regenerative potential of hearts all contribute to bioengineering difficulties [12,13].…”
Section: Introductionmentioning
confidence: 99%